Variations in phenotypic plasticity in a cosmopolitan copepod species across latitudinal hydrographic gradients - Aguilera, Victor M.; Bednaršek, Nina (Frontiers in Ecology and Evolution, 2022)
Studies assessing latitudinal variations in habitat conditions and phenotypic plasticity among populations yield evidence of the mechanisms governing differentiation in the potential to adapt to current/future habitat changes. The cosmopolitan copepod species Acartia tonsa thrives across ocean clines delimiting Seasonal (30° S-40° S) and Permanent (10°-30° S) Upwelling coastal provinces established during the middle–late Pliocene (3.6–1.8 Ma) alongshore the South East Pacific (SEP), nowadays exhibiting contrasting variability features related to several ocean drivers (temperature, salinity, pH and food availability). Latitudinal variation across the range of environmental conditions of the coastal provinces can contribute towards shaping divergent A. tonsa’s phenotypes, for example, through specific patterns of phenotypic plasticity in morphological and physiological traits, and tolerance to environmental drivers. With the aim of contributing to the understanding of these adaptive processes in a relatively little studied oceanic region, here we compared the expression of parental (i.e., adult size, egg production and ingestion rate) and offspring (i.e., egg size) traits in relation to variation in environmental habitat conditions across different cohorts of two distant (>15° latitude) A. tonsa populations inhabiting estuarine and upwelling habitats located in the Seasonal and Permanent Upwelling province, respectively. Mean conditions and ranges of variability in the habitat conditions and phenotypic plasticity of parental and offspring traits within and among cohorts of A. tonsa populations varied significantly across the different examined regions (i.e., of the Seasonal vs. Permanent). We also found significant differences in the coupling of habitat variability and traits expression, suggesting that differences in trait expressions might be related to habitat variability. The phenotypic divergence was translated to cohort-related patterns of trait trade-offs regulating reproduction and tolerance of egg production efficiency, that can jointly determine the level of plasticity, genetic structure, or local adaptation. Current findings provide novel evidence of how divergent phenotypes might sustain the population of A. tonsa across variable coastal provinces of the SEP.